Determinants of Energy Consumption In Newly Industrialised Countries of Asia - Fernandes, Karen; Reddy, Y. V. (International Journal of Energy Economics and Policy, 2020)
This study focuses on identifying the factors that lead to energy consumption in select newly industrialized countries of Asia such as China, India, Indonesia, Malaysia, Philippines and Thailand. GDP, Exchange rate, industrialization, urbanization and trade openness are the select factors identified and such data is obtained for a period from 1980-2018. To check for stationarity, ADF unit root test and PP unit root test is employed where all variables are found to be stationary at first difference. OLS regression is applied to identify which factor has an impact on energy consumption. Besides, Johansen cointegration test to establish long run relationship and VECM is employed, where all variables were found to be integrated in the long run however VECM indicated that for China and Malaysia energy consumption is able to achieve equilibrium after a shock in the previous period. To determine causal links between variables, Toda Yamamoto Causality test is applied. Results indicate that industrialization, exchange rate, financial development and trade openness causes energy consumption in China. However, in India and Thailand only industrialization causes energy consumption. GDP causes energy consumption in Indonesia and trade openness causes energy consumption in Malaysia. Keywords: Energy consumption, OLS regression, VECM, Toda Yamamoto causality JEL Classifications: O13, O20, Q43 DOI: https://doi.org/10.32479/ijeep.10725